Recommendations for the development and validation of flow cytometry‐based receptor occupancy assays. Issue 2 (22nd February 2016) - Green, Cherie L.; Stewart, Jennifer J.; Högerkorp, Carl‐Magnus; Lackey, Alan; Jones, Nicholas; Liang, Meina; Xu, Yuanxin; Ferbas, John; Moulard, Maxime; Czechowska, Kamila; Mc Closkey, Thomas W.; van der Strate, Barry W.A.; et al.
Abstract : Receptor occupancy measurements demonstrate the binding of a biotherapeutic agent to its extra‐cellular target and represent an integral component of the pharmacodynamic (PD) portfolio utilized to advance the development and commercialization of a therapeutic agent. Coupled with traditional pharmacokinetic (PK) assessments derived from serum drug concentration, receptor occupancy data can be used to model PK/PD relationships and validate dose selection decisions throughout the drug development lifecycle. Receptor occupancy assays can be even more challenging to develop than other flow cytometric methods (e.g. surface immunophenotyping). In addition to typical considerations regarding stability of the cell type of interest, stability of the target‐bound therapeutic agent and stability of the target receptor must be taken into account. Reagent selection is also challenging as reagents need to be evaluated for the potential to compete with the therapeutic agent and bind with comparable affinity. This article provides technical guidance for the development and validation of cytometry‐based receptor occupancy assays. © 2016 International Clinical Cytometry Society